A MMSE-based Beamforming Algorithm for MIMO Point-to-Point Full-Duplex Communication Systems - Tu Bui-Thi-Minh; Xung Le; Vien Nguyen-Duy-Nhat (JOIV : International Journal on Informatics Visualization, 2017)
In this paper, we focus on the precoding design for sum rate maximization while considering the effects of residual SI for point – to-point multiple input/multiple output (MIMO) Full-Duplex systems. The MMSE-based beamforming algorithm was proposed to cancel the SI. The results shown that, the self-interference cancellation is done by matrix precoding at the transmitter if the total number of transmitting antenna of two nodes is greater than the number of receiving antenna of one node. The Bit Error Rate (BER) was also evaluated in the simulation.